Pengaruh Efektivitas Penggunaan Dana BPUM, Penggunaan Software Akuntansi, dan Human Capital Terhadap Kinerja Usaha Mikro (Studi Pada Usaha Mikro Penerima Dana BPUM di Kecamatan Buleleng) - Malini, Komang Tri Widya; Herawati, Nyoman Trisna (Jurnal Akuntansi Profesi, 2021)
This research aimed at gaining empirical evidences on the effect of the effectiveness in using BPUM funds, use of accounting software, and human capital on micro business performance. This research was a causality quantitative research with the primary data collected from questionnaires and measured with likert scale. The population of this research were micro businesses that receive BPUM, which are recorded at Bank BRI Kanca Singaraja as many as 6970 micro businesses. The sampling technique used purposive sampling and obtained the number of samples as many as 100 micro enterprises. The technique of analysing data applied was multiple linear regression analysis using SPSS 16.0 for Windows. The results of this research indicate that partially the effectiveness in using BPUM funds, use of accounting software, and human capital had a positive and significant effect on the micro business performance.